2011
DOI: 10.5194/hess-15-2229-2011
|View full text |Cite
|
Sign up to set email alerts
|

Modeling subsurface transport in extensive glaciofluvial and littoral sediments to remediate a municipal drinking water aquifer

Abstract: Abstract. Few studies have been carried out that cover the entire transport process of pesticides, from application at the soil surface, through subsurface transport, to contamination of drinking water in esker aquifers. In formerly glaciated regions, such as Scandinavia, many of the most important groundwater resources are situated in glaciofluvial eskers. The purpose of the present study was to model and identify significant processes that govern subsurface transport of pesticides in extensive glaciofluvial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The resulting recharge and leaching mass time series can subsequently be coupled with a groundwater flow and pollutant transport model. Alternatively, a three-dimensional model that describes water flow and solute movement in variably saturated media could be applied (e.g., as an extension to the approach described by Bergvall et al, 2011). In the case of shallow groundwater tables, where plant roots reach into the groundwater, the coupling of models between the vadose and the saturated zone has to be implemented at an appropriate time interval (e.g., 1 d, depending on the temporal dynamics of the dominating processes); current results from the groundwater model (i.e., groundwater level and compound concentration) are then used as the lower boundary conditions for the following time step in the vadose zone model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting recharge and leaching mass time series can subsequently be coupled with a groundwater flow and pollutant transport model. Alternatively, a three-dimensional model that describes water flow and solute movement in variably saturated media could be applied (e.g., as an extension to the approach described by Bergvall et al, 2011). In the case of shallow groundwater tables, where plant roots reach into the groundwater, the coupling of models between the vadose and the saturated zone has to be implemented at an appropriate time interval (e.g., 1 d, depending on the temporal dynamics of the dominating processes); current results from the groundwater model (i.e., groundwater level and compound concentration) are then used as the lower boundary conditions for the following time step in the vadose zone model.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that although macropore processes have no dominating effect on groundwater recharge at the catchment scale, they will have significant effects on pesticide leaching to groundwater because some of the pesticides are transported rapidly downward in the soil to zones with less sorption and degradation. Bergvall et al (2011) coupled the vadose zone model HYDRUS‐1D to the groundwater flow model MODFLOW and the solute transport model MT3D to describe significant processes that govern the subsurface transport of the pesticide metabolite 2,6‐dichlorobenzoamide in a glaciofluvial esker aquifer. They reproduced the observed concentrations at the regional scale, attributed half of the model uncertainty to hydraulic conductivity in the aquifer and infiltration rate, and applied the model to optimize the location of extraction wells for remediation.…”
mentioning
confidence: 99%
“…Dichlobenil was banned in 1997, but BAM is still detected in approximately 20% of the Danish wells, and in 5% of the wells it is above the 0.1 mg/L threshold value (Thorling et al, 2013). It is also widely present in the groundwater of many other countries (e.g., Bergvall et al, 2011 and references therein), although it is not monitored regularly in most countries outside Northern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two sets of K fs values, those provided by the drive point GP approach are considered more accurate because of the soil's medium-coarse sand texture and negligible silt and clay content. Supporting this is a modelling study by Bergvall et al (2011) who used calibration of the HYDRUS-1D water-solute transport model to estimate 2.89 × 10 − 4 m s − 1 ≤ K fs ≤ 4.63 × 10 − 4 m s − 1 for the top 0.9 m at the field site, which includes the range of drive point GP results (i.e. 2.87 × 10 − 4 m s − 1 ≤ K fs ≤ 3.74 × 10 − 4 m s − 1 , Table 4).…”
Section: Comparison Of α* and K Fs From The Drive Point And Original mentioning
confidence: 86%